Cobalt and magnesium ferrite nanoparticles: preparation using liquid foams as templates and their magnetic characteristics - Bala, Tanushree; Sankar, C. R.; Baidakova, Marina; Osipov, V.; Enoki, Toshiaki; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Langmuir, 2005)
An easy and convenient method for the synthesis of cobalt and magnesium ferrite nanoparticles is demonstrated using liquid foams as templates. The foam is formed from an aqueous mixture of an anionic surfactant and the desired metal ions, where the metal ions are electrostatically entrapped by the surfactant at the thin borders between the foam bubbles and their junctions. The hydrolysis is carried out using alkali resulting in the formation of desired nanoparticles, with the foam playing the role of a template. However, in the formation of ferrites with the formula MFe2O4, where the metal ion and iron possess oxidation states of +2 and +3, respectively, forming a foam from a 1:2 mixture of the desired ionic solutions would lead to a foam composition at variance with the original solution mixture because of greater electrostatic binding of ions possessing a greater charge with the surfactant. In our procedure, we circumvent this problem by preparing the foam from a 1:2 mixture of M2+ and Fe2+ ions and then utilizing the in situ conversion of Fe2+ to Fe3+ under basic conditions inside the foam matrix to get the desired composition of the metal ions with the required oxidation states. The fact that we could prepare both CoFe2O4 and MgFe2O4 particles shows the vast scope of this method for making even multicomponent oxides. The magnetic nanoparticles thus obtained exhibit a good crystalline nature and are characterized by superparamagnetic properties. The magnetic features observed for CoFe2O4 and MgFe2O4 nanoparticles are well in accordance with the expected behaviors, with CoFe2O4 particles showing higher blocking temperatures and larger coercivities. These features can easily be explained by the contribution of Co2+ sites to the magnetocrystalline anisotropy and the absence of the same from the Mg2+ ions.

Cure characteristics and dielectric properties of magnetic composites containing strontium ferrite - Soloman, M. A.; Kurian, P.; Anantharaman, Maliemadom R.; Joy, Pattayil Alias (Journal of Elastomers and Plastics, 2005)
Hexagonal strontium ferrite (SrFe12O19) powders were synthesized by the conventional ceramic techniques. They were then characterized by the X-ray diffraction method and incorporated in the natural rubber matrix according to a specific recipe for various loadings of ferrite to produce rubber ferrite composites (RFCs). The processability of these compounds was determined by evaluating the cure characteristics namely, scorch time, cure time, minimum and maximum torque. The evaluation of the dielectric properties of ceramic strontium ferrite (SrF), natural rubber gum vulcanizate, and RFCs were done with the help of a Hewlett Packard (HP) impedance analyzer. The magnetic properties of these composites were studied using a Vibrating Sample Magnetometer (VSM). The effect of carbon black on the processability, and the magnetic and dielectric properties were also studied by the incorporation of carbon black into these composites. It has been found that the addition of these ferrites and carbon black does not affect the processability of these composites, whereas the physical properties are found to be modified. From the magnetic and dielectric measurements it has been found that flexible magnets having appropriate dielectric strength can be prepared by the incorporation of appropriate amount of SrF and carbon black in the natural rubber matrix.
Keywords: hexagonal ferrites; Magnetic materials; permanent magnets; rubber ferrite composites (RFCs); strontium ferrite

Characterization of nanosized NiZn ferrite powders synthesized by an autocombustion method - Deka, Sasanka; Joy, Pattayil Alias (Materials Chemistry and Physics, 2006)
Nanocrystalline Ni0.5Zn0.5Fe2O4 with average particle size of similar to 9 nm has been synthesized by an autocombustion method and characterized by powder XRD, TEM and room temperature magnetic measurements. High room temperature magnetization comparable to that of the bulk material is obtained for the nanosized powders annealed at 800 degrees C, with a maximum particle size of similar to 54 nm. The results show that optimum properties can be achieved for NiZn ferrite powders synthesized by the present autocombustion method and processed at relatively lower temperatures. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Magnetic materials; magnetic properties; Oxides

Colossal thermoelectric power in Gd-Sr manganites - Sagar, S.; Ganesan, V.; Joy, Pattayil Alias; Thomas, Senoy; Liebig, A.; Albrecht, M.; Anantharaman, Maliemadom R. (EPL, 2010)
Manganites belonging to the series Gd(1-x)Sr(x)MnO(3) (x=0.3, 0.4 and 0.5) were prepared by wet solid-state reaction and their thermoelectric power was evaluated. Thermoelectric power measurements revealed a peak value at similar to 40 K. All the samples exhibited a colossal thermopower at similar to 40K and in that Gd(0.5)Sr(0.5)MnO(3) exhibited a maximum value of similar to 35 V/K, which is the largest reported for these class of materials at this temperature. Temperature-dependent magnetisation measurements showed that the samples exhibit a phase transition from paramagnetic to spin-glass-like state at these temperatures. Plausible mechanisms responsible for the observed colossal thermoelectric power in Gd-Sr manganites are discussed. Copyright (C) EPLA, 2010

Contact potential induced enhancement of magnetization in polyaniline coated nanomagnetic iron oxides by plasma polymerization - Sethulakshmi, N.; Sooraj, V.; Sajeev, U. S.; Nair, Swapna S.; Narayanan, T. N.; Joy, Lija K.; Joy, Pattayil Alias; Ajayan, Pulickel M.; Anantharaman, Maliemadom R. (Applied Physics Letters, 2013)
The present work derives motivation from the so called surface/interfacial magnetism in core shell structures and commercial samples of Fe3O4 and gamma Fe2O3 with sizes ranging from 20 to 30 nm were coated with polyaniline using plasma polymerization and studied. The High Resolution Transmission Electron Microscopy images indicate a core shell structure after polyaniline coating and exhibited an increase in saturation magnetization by 2 emu/g. For confirmation, plasma polymerization was performed on maghemite nanoparticles which also exhibited an increase in saturation magnetization. This enhanced magnetization is rather surprising and the reason is found to be an interfacial phenomenon resulting from a contact potential. (C) 2013 AIP Publishing LLC.

Citrate modified beta-cyclodextrin functionalised magnetite nanoparticles: a biocompatible platform for hydrophobic drug delivery - Jayaprabha, Kunnoth N.; Joy, Pattayil Alias (RSC Advances, 2015)
Water-dispersible magnetite nanoparticles functionalized with citric acid (CIT) modified beta-cyclodextrin (CD) are prepared and curcumin (CUR) is loaded inside the cavity of CD. The CUR loading capacity of CD-CIT functionalized magnetite nanoparticles is found to be much larger than that of CD alone as well as the CD-CIT conjugate. The release profile of curcumin is found to follow zero order kinetics at the physiological pH, and thus, can release CUR at a constant rate, after the initial burst release. Relaxivity studies using NMR showed that the functionalized nanoparticles are suitable for contrast enhancement in MRI. Thus, the water-dispersible, CIT modified beta-CD functionalized magnetite nanofluid is an efficient carrier for water insoluble curcumin, and can be used for magnetic drug targeting/delivery as well as for contrast enhancement in MRI due to the superparamagnetic magnetite core.

Co3O4 nanorods-efficient non-noble metal electrocatalyst for oxygen evolution at neutral pH - Ramsundar, Rani M.; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Joy, Pattayil Alias (Electrocatalysis, 2015)

Correlations between structure, microstructure, density and dielectric properties of the lead-free ferroelectrics Bi0.5(Na,K)0.5TiO3 - Anjali, K.; Ajithkumar, Thalasseril G.; Joy, Pattayil Alias (Journal of Advanced Dieletrics, 2015)

Cross over from 3D variable range hopping to the 2D weak localization conduction mechanism in disordered carbon with the extent of graphitization - Raj, Kovummal Govind; Joy, Pattayil Alias (Physical Chemistry Chemical Physics, 2015)
The changes in the electrical transport properties and mechanism of conduction in disordered carbon, with the extent of graphitization, are studied and discussed. With heat treatment induced graphitic ordering, the electrical properties are considerably modified, inducing a crossover from strong localization to weak localization behavior. Accordingly, the conduction mechanism is modified from the 3-dimensional variable range hopping (3D VRH) model to the 2-dimensional weak localization (2D WL) model. Results show that carrier-carrier and carrier-phonon interactions play major roles in developing the weak localization behavior with the extent of graphitization.